M. V. Nadkarni. Farmer's Movements in India. New Delhi: Allied Publishers Pvt. Ltd., 1987.237 pp.,Price: (hardbound edition) Rupees (Indian) 100.00. (The Pakistan Development Review, 1988)
This book is a comprehensive analysis of farmers' movements in India with a focus on the movements in Tamil Nadu, Maharashtra, Punjab and Karnatka. It examines the economic, social and political aspects of the farmers' struggle for a better deal within regional and national perspectives and evaluates the potential impact of these struggles on economic development in general, and on rural development, in particular. In a most competent way the author has presented the current state of the debate on the subject. He deals exhaustively with the subject of agricultural price policy and argues against the proposition that favourable price-setting for farm products is adequate to alleviate rural poverty. A better way to tackle this problem is to improve the per capita output in the rural sector, since the root cause of the problem is not unfavourable terms of trade but the increasing proportion of land holdings, which are economically not viable. Agricultural price policy is analyzed within the context of class relations, which enables to establish a link between the economic and political demands of the farmers. This analysis leads the author to conclude, that in contrast with the peasants' movements in India, which helped to break up the feudal agrarian set-up, the recent farmers' movements, with a few exceptions, have little revolutionary content. Their leadership has been appropriated by the rich landowners, who have transformed the movements into a lobby for advancing their own interests, within the existing power structure, to the neglect of the poorer peasantry.